COVID-19 and post-traumatic stress disorder among nurses: a descriptive cross-sectional study in a COVID hospital - Marcomini, Ilaria; Agus, Cristina; Milani, Laura; Sfogliarini, Roberto; Bona, Annamaria; Castagna, Marco (La Medicina del Lavoro, 2021)
Background: In March 2020, the World Health Organisation (WHO) declared the novel coronavirus (COVID-19) outbreak a global pandemic. Healthcare professionals directly involved in diagnosing, treating and caring for patients with COVID-19 are at risk of developing post-traumatic stress disorder (PTSD). Objective: This study investigated the prevalence of PTSD among nurses working in a COVID hospital and evaluated associated factors. Methods: A descriptive cross-sectional study was conducted at Crema Hospital and the Impact of Event Scale – Revised (IES-R) was administered. Data collection took place from July to September 2020, during which 275 questionnaires were distributed. Results: Of the total sample, 39.88% received a provisional PTSD diagnosis deserving of further analysis. Nurses stated that they were predominantly overwhelmed by intrusive thoughts (M = 1.55). Working in the emergency department during the COVID-19 pandemic (OR=2.40; p=0.02), irregular work shifts (OR=5.41; p=0.01) and coming from a mental health ward (OR=3.80; p=0.02) increased the risk of receiving a provisional PTSD diagnosis. Our findings showed significantly higher IES-R scores among women than among men (p = 0.01). The activities that caused the most distress were related to technical skills required for managing ventilation and intubation devices. Conclusions: The results of the study highlighted the presence of considerable psychological distress in the sample. There is an urgent need to monitor the short- and long-term consequences of the COVID-19 pandemic and implement early intervention measures.